Rechallenge therapy versus tyrosine kinase inhibitor (TKI) for advanced metastatic colorectal cancer: a retrospective study - Chenming Liu; Jintao Chen; Yuxing Liu (Scientific Reports)
Abstract Currently, the standard third-line treatment options for advanced metastatic colorectal cancer (mCRC) include regorafenib, fruquintinib, and trifluridine/tipiracil (TAS-102), but these drugs have limited clinical efficacy. This study aims to evaluate the efficacy and survival outcomes of tyrosine kinase inhibitor (TKI) versus chemotherapy rechallenge in third-line treatment for advanced mCRC patients. From January 2019 to December 2022, 107 patients met the inclusion criteria. After 1:1 matching, there were 34 patients in both the TKI and rechallenge groups. Cox regression analysis was performed to identify independent predictive factors. The result indicated that Eastern Cooperative Oncology Group (ECOG) score of 0–1 (hazard ratio [HR] = 0.03, 95% confidence interval [CI]: 0.01–0.17; P < 0.001) and chemotherapy rechallenge (HR = 0.43, 95% CI: 0.23–0.79; P = 0.007) were independent protective factors for overall survival (OS). Patient-Generated Subjective Global Assessment (PG-SGA) score of 0–3 (HR = 0.43, 95% CI: 0.23–0.80; P = 0.008), progression-free survival (PFS) of frontline treatment (HR = 0.66, 95% CI: 0.43-1.00, P = 0.047) and chemotherapy rechallenge (HR = 0.42, 95% CI: 0.24–0.73; P = 0.002) were independent protective factors for PFS. Kaplan-Meier survival analysis showed that the median OS in the rechallenge group was 13.2 months (95% CI: 9.6–19.3), compared with 7.7 months (95% CI: 6.5–14.5) in the TKI group, with a statistically significant difference (HR = 0.47, 95% CI: 0.26–0.86; P = 0.013). The median PFS for the rechallenge group was 5.0 months (95% CI: 4.3–6.7), compared with 3.4 months (95% CI: 2.7–4.8) in the TKI group, with a statistically significant difference too (HR = 0.54, 95% CI: 0.32–0.91; P = 0.019). Furthermore, subgroup analysis showed that in Group A, the rechallenge group also had superior median OS and PFS compared with the TKI group. In conclusion, while TKIs are the current standard for third-line treatment in mCRC patients, chemotherapy rechallenge is a more effective option for patients who have achieved disease control in the first two lines of treatment.